An analytical study of the facts of the phenomenon of violence and aggression in the Iraqi courts under the system of globalization - Hadi, aseer (Journal of Physical Education, 2012)
Section One contains the importance of research in terms of a system of globalization the world and its effects on sports stadiums in all disciplines and sports competitions Among the manifestations of globalization sports is the increase in violence in competitions and his own after the events of past and present in Iraq and the deteriorating security situation and the lack of adequate protection of the courts, players and even the public and the Pena what causes this phenomenon, either in Part II has contained Identification of aggression and violence in general terms what is the concept of infections in the sport and the researcher ways of how to treat this phenomenon, which reduces the development of sport in Qtrna, and in Part III, which included the research methodology and procedures of field sample in terms of research and exploratory experience and tools used in this research as well as the most important statistical methods.In Part Four was viewing the results and discussion obtained by the researcher through the standard deviations and circles arithmetic and percentages, which indicates that the system of globalization basic role in the dissemination of mathematical concepts of good and Ethics Commissioner that rejects the use of violence in sports stadiums, and in section V has been the most important conclusions and recommendations reached by the researcher through the research.